Principles of sustainable living a new vision for health, happiness, and prosperity - Jurin, Richard R. (Richard Robert) 1953- (Human Kinetics, 2012)
No one can argue against wanting a better quality of life--and Principles of Sustainable Living: A New Vision for Health, Happiness, and Prosperity provides keen insight into how to achieve that so that individuals, communities, and the environment all come out winners. This transdisciplinary text presents principles of sustainability, develops environmental literacy, and expands awareness of sustainable practices that will steer readers toward a lifestyle that they, as well as the entire planet, will benefit from. Author Richard Jurin, an expert in sustainable living, has written numerous publications on sustainable development, business leadership for sustainability, and related issues. He takes students beyond sustainability's traditional "triple bottom line" of people, profit, and planet to a quadruple paradigm that includes economic, sociocultural, psychological, and ecological aspects of sustainability. The text offers: principles of sustainability that support a range of university courses in multiple disciplines; a systems approach to sustainability that reflects worldwide views and values; case studies, personal reflections, and applications that help students understand their status and the challenges of the future; and guidelines for developing sustainable living through daily choices. The book explores the mind-sets that have created the modern, consumer-based world we live in, exposing environmental and societal global problems as it does; lays out new ways of thinking, championing sustainable thinking as a prerequisite for living a healthy, happy, vibrant life that benefits the planet; and details positive options for living a sustainable lifestyle. Readers will be able to understand sustainability from a broad perspective--how it can improve their lives, resolve environmental problems, and improve the condition of the planet for all life. Principles of Sustainable Living points out the problems and challenges we face individually and as caretakers of our planet and offers lifestyle approaches that can sustain quality of life long into the future.